Implementation Of The Policy Of Equalizing Structural Positions (JA) To Functional Positions (JF) In Efforts To Enhance Motivation, Performance, And Career Development Of Employees Of The National Policy Strategy Agency (BSKDN) - Riana Dewi; M. Ali Iqbal (Publikasi Indonesia, 2023)
The purpose of this research is to analyze the Implementation of the Policy of Equalizing Structural Positions (JA) to Functional Positions (JF) in efforts to enhance the motivation, performance, and career development of employees at the National Policy Strategy Agency (BSKDN). The participants in this research are former Structural Officials of Eselon III and IV who were affected by the equalization of positions at BSKDN, totaling 10 individuals. The method used in this research is qualitative descriptive, collecting field data through interviews with informants and participants, observing the research subjects, and studying documentation related to the theme being researched. The study's findings reveal that BSKDN Kemendagri has taken steps to implement the equalization policy by conducting socialization and providing facilitation to all officials impacted by the equalization of positions. In the process of implementing the division of positions at BSKDN, clear communication and available bureaucratic structure have been evident, though further resource management is still required. The disposition has been executed, enabling the implementation of the policy of equalizing positions at BSKDN to proceed smoothly. However, some challenges were identified in the process, requiring further handling and management.